Phytoplankton structure in dry and rainy seasons in the gulf of Papagayo, Costa Rica - Loza-Álvarez, Sandra (2018)
In order to study the phytoplankton structure in the gulf of Papagayo, 2 sampling cruises were conducted in February and June of 2017, and hydrographic information was additionally analyzed. The phytoplankton composition was dominated in both months by diatoms, dinoflagellates, cyanobacteria and flagellates. The fraction of diatoms contributed mainly to the phytoplankton structure with 41 taxa, followed by dinoflagellates with 20 taxa. In diatoms, the genera with the greatest contribution to diversity and frequency were Rhizosolenia sp., Guinardia sp., and Thalassiosira sp. In the case of dinoflagellates, Tripos furca predominated in station 20 located in Culebra Bay, while Gyrodiniumspirale was frequent, as well as genera Gymnodinium sp., Gyrodinium sp., and Amphidinium sp. Cyanobacteria were mainly composed by genera Analysis sp. and Chroococcus sp. and haptoficeas and flagellates, by the Coccolitoforids and the genus Chrysocromulina sp., respectively. In February the phytoplankton concentration varied between 326 and 1063 cells mL-1, and in June between 653 and 1041 cells mL-1, with mesotrophic characteristics in both seasons. The gulf’s hydrography is regulated by the annual rainfall cycle and the seasonal coastal upwelling of Papagayo. In February, as opposed to October, surface temperature decreased by 3°C, salinity increased by 2 and chlorophyll-a concentration increased by 0.5 mg .m-3. Warmer waters, with lower saline and chlorophyll-a concentrations in October (T > 29°, S < 32.2, Chl-a < 0.5 mg m-3) are opposed to February results.